Optimizing Application Portfolios Through TIME Analysis in an Indonesian Telecommunications Company - Muhammad Faudzan Khairunasi Dzisyauqi; Astari Retnowardhani (Politeknik Siber Cerdika Internasional, 2026)
Background: Digital transformation has increased the strategic importance of application portfolios as key enablers of organizational performance; however, many organizations continue to operate legacy and redundant applications, which reduce efficiency and increase operational and maintenance costs. Objective: This study examines application portfolio optimization in an Indonesian telecommunications company by applying Enterprise Architecture principles through Application Portfolio Management (APM). Methods: APM employs the TIME (Tolerate, Invest, Migrate, Eliminate) Analysis framework. A case study methodology was adopted by combining stakeholder interviews, Focus Group Discussions (FGDs), direct observations, and architectural repository data covering 553 enterprise applications. Each application was assessed based on Business Value and Technical Value using a four-point Likert scale. Results: TIME Analysis revealed that 269 applications were positioned in the Invest quadrant, reflecting strong business relevance and satisfactory technical conditions, while 85 applications were categorized under Eliminate, indicating significant potential for application rationalization. The analysis classified 269 applications (48.6%) as Invest, 125 applications (22.6%) as Tolerate, 73 applications (13.2%) as Migrate, and 85 applications (15.4%) as Eliminate, resulting in a Portfolio Health Index of 71.2%. Conclusion: These findings confirm that TIME Analysis, operationalized through an Enterprise Architecture repository, provides an objective and data-driven basis for application portfolio decision-making, extends the Application Portfolio Management literature by linking architecture repositories with portfolio rationalization, and strengthens Business–IT alignment in telecommunications organizations.